KAJIAN BIOETIKA DALAM ETIKA BERPROFESI ARSITEK - Putu Gde Ery Suardana (Universitas Dwijendra, 2016)
Architect as a( profession by a part society std as sum ed only design picture, so that in carry out only finish what be task owner. Therefore, oftentimes happen in carry out as architect disagree with code ethics architect, finally in work do not total applies the profesionality. A architect should be apply the profession with be espoused integrity and spearhead to present best work to owner and society,with enrich environment and culture. Based on the mentioned above, in this paper tried to discuss professional ethics studied to through bioethics.Key words : professional ethics, architect, bioethics